(untitled) (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2014)
Growth models have an important place in the economics. These models try to reflect the behavior of an economy so that we can understand and analyze the growth mechanism in the economy. Growth theory first focusing on the production function tried to explain the growth in the physical production. However, in the real world, if the saving part of that production is not channeled into physical capital, the scenario of the early growth models cannot reflect the real world. In this sense, Tobin model has made the first step including money option for the individual saving portfolio and turned the growth model into the monetary growth model. In this study, we revisited important discussions on Tobin model and by conducting a critical analysis on the critically important features we are hoping to attract attention to the uncompleted arguments. In this manner we evaluate that the stableness of the equilibrium can be translated differently so that point needs to be cleared in described classification. The critical first step of articulation of saving portfolio can put the model in a strategic reference point situation as we would like to underline.